The role of tissue-resident memory T cells as mediators for response and toxicity in immunotherapy-treated melanoma—two sides of the same coin? - Reschke, Robin; Deitert, Benjamin; Enk, Alex H.; Hassel, Jessica C. (Frontiers in Immunology, 2024)
Tissue-resident memory T cells (TRM cells) have become an interesting subject of study for anti-tumor immunity in melanoma and other solid tumors. In initial phases of anti-tumor immunity, they maintain an immune equilibrium and protect against challenges with tumor cells and formation of primary melanomas. In metastatic settings, they are a prime target cell population for immune checkpoint inhibition (ICI) because they highly express inhibitory checkpoint molecules such as PD-1, CTLA-4 or LAG-3. Once melanoma patients are treated with ICI, TRMs cells residing in the tumor are re-activated and expand. Tumor killing is achieved by secreting effector molecules such as IFN-γ. However, off-target effects are also observed. Immune-related adverse events, such as those affecting barrier organs like the skin, can be mediated by ICI-induced TRMs cells. Therefore, detailed understanding of this memory T cell type is obligatory to better guide and improve immunotherapy regimens.